Kualitas Biologi Beberapa Mata Air Di Desa GedongjetisKecamatan Tulung Klaten Dengan Metode MPN - Rohmah, Anisa Nur; , Triastuti Rahayu, S.Si., M.Si (2015)
Gedongjetis is one of the villages in the district of Tulung Klaten potentially springs that much, because the location of the topography between Mount Merapi and a thousand mountains. The springs are located in the village of Gedongjetis tested based on water quality in terms of biological parameters, namely total coliform and fecal coliform. The method used is the MPN method includes test slightly its estimate and discernment. Tests using the series tube 3-3- 3 and inoculum 10ml, 1 ml, 0.1 ml. The results showed that the springs Gedongjetis exceeds the raw quality of Class I with fecal coliform MPN values> 100/100 ml, water from the spring Bulu and Beji including Class I fecal coliform MPN value <100/100 ml. Spring Gedongjetis can not be used as water that can be consumed directly, but springs Bulu and Beji can be consumed directly. These results are based on Government Regulation No. 82 in 2001. However, if consumed for drinking water in daily life without immediate treatment, the three springs exceeds the maximum allowed for the MPN value> 0/100 ml (Health Regulation No.492 in 2010).